2005
DOI: 10.3748/wjg.v11.i13.1965
|View full text |Cite
|
Sign up to set email alerts
|

Amylase level in extrahepatic bile duct in adult patients with choledochal cyst plus anomalous pancreatico-biliary ductal union

Abstract: The results support the notion that amylase has a particular role in the onset of symptoms, and suggest that a large amount of biliary amylase induces early onset of symptom, thereby making early diagnosis possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…17 In our present study, as the size of choledochal cyst increased, the grade of inflammation was raised and anastomotic stricture increased. The high grade of inflammation was related with cyst wall thickening, but no relation with fibrosis grade.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…17 In our present study, as the size of choledochal cyst increased, the grade of inflammation was raised and anastomotic stricture increased. The high grade of inflammation was related with cyst wall thickening, but no relation with fibrosis grade.…”
Section: Discussionsupporting
confidence: 55%
“…In children, there are different levels of biliary amylase, [17][18][19] and postoperative complications are less common than in adults. 5,6,[8][9][10]16,20,21 Yamataka et al 20 studied anastomotic stricture that developed in four patients who underwent operation under 19 years of age, respectively, and found that increase of age had increased incidence because there were no anastomotic strictures in 145 children who underwent operation at 5 years or younger.…”
Section: Discussionmentioning
confidence: 99%
“…The biliary amylase levels in PBM are often at least 10,000 IU/L (Table 1) [26,[62][63][64]. However, patients with bile duct stones or those with decreased exocrine pancreatic function may sometimes not show elevated biliary amylase levels even if they suffer from PBM [65].…”
Section: Commentsmentioning
confidence: 99%
“…A lack of sphincter function, due to abnormal anatomical junction of the pancreaticobiliary ductal system, in combination with a pressure difference between the duodenum and the sphincter of Oddi is proposed to convey the reflux of pancreatic juice into the biliary system [37,46]. Numerous authors suggest a sequence of pancreatobiliary reflux, inflammation, dysplasia followed by biliary stasis, which finally leads to increased mutagenicity and carcinoma [15,45,[47][48][49]. Molecular events in carcinogenesis are still poorly understood and provided elsewhere [8].…”
Section: Malignancymentioning
confidence: 99%